2005
DOI: 10.1158/0008-5472.can-05-1965
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dietary Triterpene Lupeol Induces Fas-Mediated Apoptotic Death of Androgen-Sensitive Prostate Cancer Cells and Inhibits Tumor Growth in a Xenograft Model

Abstract: In prostate cancer, a fine balance between cell proliferation and apoptotic death is lost, resulting in increased cellular mass and tumor progression. One approach to redress this imbalance and control this malignancy is its preventive intervention through the use of dietary natural agents. Here, we investigated the growth-inhibitory effect and associated mechanisms of Lupeol, a triterpene present in fruits and vegetables, in androgen-sensitive human prostate cancer cells. Lupeol treatment resulted in signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 38 publications
2
113
1
5
Order By: Relevance
“…The small interfering RNA-mediated silencing of the Fas gene and inhibition of caspase-6, caspase-8, and caspase-9 by their specific inhibitors further confirmed that lupeol specifically activates the Fas receptor-mediated apoptotic pathway [41]. Furthermore, combination of anti-Fas monoclonal antibody and lupeol resulted in higher cell death compared with the additive effect of the two compounds alone, suggesting a synergistic effect that can be exploited against CaP.…”
Section: Lupeolmentioning
confidence: 66%
See 4 more Smart Citations
“…The small interfering RNA-mediated silencing of the Fas gene and inhibition of caspase-6, caspase-8, and caspase-9 by their specific inhibitors further confirmed that lupeol specifically activates the Fas receptor-mediated apoptotic pathway [41]. Furthermore, combination of anti-Fas monoclonal antibody and lupeol resulted in higher cell death compared with the additive effect of the two compounds alone, suggesting a synergistic effect that can be exploited against CaP.…”
Section: Lupeolmentioning
confidence: 66%
“…It possesses strong anti-inflammatory, antiarthritic, antimutagenic, and antimalarial activity and has been used for the treatment of various diseases [40]. Recent data from our laboratory and others suggest that lupeol possesses potent anti-cancer activities in vitro and in vivo systems [41]. We have shown that lupeol treatment resulted in significant inhibition of cell viability of LNCaP and CWR22Rν1 androgen-sensitive prostate cancer cells with minimal effect on normal prostate epithelial cells [41].…”
Section: Lupeolmentioning
confidence: 78%
See 3 more Smart Citations